FAKTA CERITA DALAM NOVEL "LEBIH SENYAP DARI BISIKAN" KARYA ANDINA DWIFATMA: STRUKTUR ROBERT STANTON - Yuni Novalina Siringoringo; Ikhwanuddin Nasution; Haris Sutan Lubis (Jurnal Bahasa Indonesia Prima (BIP), 2024)
ABSTRACK - The results of this research aim to describe the facts of the story in the novel More Senyap dari Bisikan by Andina Dwifatma. This research includes library research, while the method used is qualitative descriptive analysis. The data sources used are words, sentences, discourse in the novel More Senyap Than Bisikan by Andina Dwifatma. The approach used is Robert Stanton's structural approach. The results of this research are as follows, the story facts consist of the plot, characters and setting featured in the novel. The plot used in the novel Silent Than a Whisper is a forward plot. The characters in the novel are obsessive, worried and over thinker, hardworking, The setting in the story is still in the same city, the setting used is: Amara and Baron's house, the time setting used is: morning, afternoon, afternoon and evening. The social setting in the novel is: beliefs, ways of thinking, living habits, traditions. Key words: Robert Stanton structure, story facts, novel